Research priorities in trans health: a Delphi-study - Lucie Jurek; Lucie Jurek; Marie De la Chenelière; Marion Lapoirie; Paul Neuville; Paul Neuville (Frontiers Media S.A., 2024)
PurposeProgress has been made in understanding trans health needs, but research priorities are often set by policy or healthcare professionals without trans input, which may not reflect public needs. Our study sought to identify trans health research priorities in France from both researchers and the trans community.MethodsExpert stakeholders (health and social sciences professionals, trans individuals, and their families) answered a three-round Delphi survey on trans health research priorities. The first round involved an open-ended questionnaire, analyzed qualitatively. In the second round, participants ranked research propositions from round one using a Likert scale. The study's second phase involved a two-hour workshop with experts and trans individuals.Results53 participants (32% trans individuals/relatives, 60% health professionals) contributed 217 responses to open-ended questions, leading to 44 research priorities. After the two voting rounds, a total of five proposals reached a strong consensus cut-off and were considered as the main research priorities: evaluation of the effect of puberty blocker use in trans children and adolescents (95%), evaluation of the effect of supporting trans children and adolescents (92%), study of the support systems available for trans youth and their parents (86%), persistence of trans identity around puberty (prevalence, persistent persons characteristics) (86%), and needs assessment survey of the support for adolescents and their families (83%). Thirteen other proposals were considered moderate priorities.ConclusionThe main consensus in our French study concerned research on trans-youth care and support needs. Our results may guide further trans-health research that meets the public's needs and desires.